PENGEMBANGAN PROTOTYPE MENGGAMBAR SEDERHANA MENGGUNAKAN TEORI ENGAGEMENT DENGAN PENGUJIAN TAM UNTUK ANAK PRASEKOLAH - Shelvia Tressia (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Information Communication Technology (ICT) plays an important role in the development and terms of the education needs of preschool children. Not inevitable that in this modern age, older children need technology that will accompany her in the process of learning and teaching. Drawing is a process of learning that can be supported by technology. In fact the technology is there to help the process of learning to draw is not easy to use by preschoolers. Therefore, it takes a prototype that can assist children in learning to use technology such as computers. This research aims to develop a simple drawing using the prototype theory of Engagement by testing the Technology Acceptance Model. Research methods include two stages. The first stage was the creation of the prototype and the second stage is testing prototypes. In the stage production of prototype research participants amounted to two teachers namely kindergarten teacher A and B. Interview given to obtain data about how to learn to draw in children kindergarten. Second stage, testing prototype using participants totalling 21 kindergarten students A and B. Test color and image recognition is given to know the child's knowledge before and after using the prototype. A questionnaire given to calculate the data reception prototype. The research results obtained are drawing a simple prototype can increase understanding of the application of drawing, perceived ease of use and perceived usefulness can affect behavioral intention to use prototype. Key words Preschoolers, engagement, drawing, prototype, technology acceptance models.